National Consensus Statement for the Management of Hypothyroidism in Nepal - Shrestha, Dina (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Hypothyroidism, most common of all the thyroid disorders, is estimated to have a worldwide prevalence of up to 4.6%. Although epidemiological data of hypothyroidism in Nepal is not available, several hospital-based studies have indicated a high prevalence ranging from 8 to 11.6%. Currently, there are no national guidelines in Nepal for the management of hypothyroidism. This document reviews the current international and regional guidelines and summarizes a consensus statement specifically for Nepal based on experts’ opinion and evidence from literature.